2014
DOI: 10.3855/jidc.3398
|View full text |Cite
|
Sign up to set email alerts
|

Pfcrt mutant haplotypes may not correspond with chloroquine resistance

Abstract: Introduction: Chloroquine resistance in Plasmodium falciparum is associated with mutations in pfcrt and pfmdr1 genes. The frequency distribution of pfcrt K76T and pfmdr1 N86Y mutations and their association with chloroquine susceptibility was studied in an endemic area along the Indo-Bangladesh border. Methodology: A single-arm prospective study of clinical and parasitological responses in P. falciparum malaria patients to chloroquine was conducted in vivo. PCR-RFLP assay was used to detect pfcrt K76T and pfmd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…In addition, one isolate that was wild type at the pfcrt locus had a CQ IC 50 of 124.8 nM, which may indicate the influence of factors other than pfcrt haplotype in CQ resistance, and so warrants further study. In summary, our results indicate a strong association between pfcrt genotype and drug sensitivity, and are consistent with previous studies [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, one isolate that was wild type at the pfcrt locus had a CQ IC 50 of 124.8 nM, which may indicate the influence of factors other than pfcrt haplotype in CQ resistance, and so warrants further study. In summary, our results indicate a strong association between pfcrt genotype and drug sensitivity, and are consistent with previous studies [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…This underscores the notion of K76T as an insufficient predictor of CQR status and supports the fact that CQ resistance or susceptibility can depend on additional PfCRT substitutions (e.g. C101F, L272F, C350R, or in this case A144F), even when K76T is present [22,6062]. …”
Section: Resultssupporting
confidence: 67%
“…We note that parasites encoding Cam734 F144A PfCRT retained K76T as well as 7 other mutations [7]. The clear importance of mutations other than K76T in contributing to CQR can help explain, in areas where novel PfCRT variants have arisen, why the K76T mutation predicts clinical CQR with good sensitivity but only moderate specificity [17,62]. Another important factor driving the reduced specificity of the K76T marker is patient immunity, which in higher-transmission settings of Africa is known to help resolve CQ-resistant infections in CQ-treated patients [78].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in north-east India [2], [10] have also reported CQ resistance in more than 80% isolates of Pf indicating non-effectiveness of CQ over the region. Although pfmdr -1 has been thought to affect CQ resistance, however, no correlation between the prevalence of pfcrt mutation and pfmdr -1 point mutation was noted in the present study, which was also observed in earlier studies further strengthening the doubt over its involvement in CQ resistance [32], [33].…”
Section: Discussionsupporting
confidence: 51%